14
$\begingroup$

I want to factorize the polynomial $x^3+y^3+z^3-3xyz$. Using Mathematica I find that it equals $(x+y+z)(x^2+y^2+z^2-xy-yz-zx)$. But how can I factorize it by hand?

$\endgroup$
9
$\begingroup$

Use Newton's identities:

$p_3=e_1 p_2 - e_2 p_1 + 3e_3$ and so $p_3-3e_3 =e_1 p_2 - e_2 p_1 = p_1(p_2-e_2)$ as required.

Here

$p_1= x+y+z = e_1$

$p_2= x^2+y^2+z^2$

$p_3= x^3+y^3+z^3$

$e_2 = xy + xz + yz$

$e_3 = xyz$

$\endgroup$
15
$\begingroup$

Consider the polynomial $$(\lambda - x)(\lambda - y)(\lambda - z) = \lambda^3 - a\lambda^2+b\lambda-c\tag{*1}$$ We know $$\begin{cases}a = x + y +z\\ b = xy + yz + xz \\ c = x y z\end{cases}$$ Substitute $x, y, z$ for $\lambda$ in $(*1)$ and sum, we get $$x^3 + y^3 + z^3 - a(x^2+y^2+z^2) + b(x+y+z) - 3c = 0$$ This is equivalent to $$\begin{align} x^3+y^3+z^3 - 3xyz = & x^3+y^3+z^3 - 3c\\ = & a(x^2+y^2+z^2) - b(x+y+z)\\ = & (x+y+z)(x^2+y^2+z^2 -xy - yz -zx) \end{align}$$

$\endgroup$
  • $\begingroup$ You've just proved Newton's identities... $\endgroup$ – lhf Oct 29 '13 at 11:23
  • 4
    $\begingroup$ @lnf sort of. but for Newton's identities of this low degree, it will be useful to explicitly spell out everything. $\endgroup$ – achille hui Oct 29 '13 at 11:29
13
$\begingroup$

\begin{align}x^3+y^3+z^3-3xyz & = x^3+y^3+3x^2y+3xy^2+z^3-3xyz-3x^2y-3xy^2 \\ & =(x+y)^3+z^3-3xy(x+y+z)\\ &= (x+y+z)((x+y)^2+z^2-(x+y)z)-3xy(x+y+z) \\ & =(x+y+z)(x^2+2xy+y^2+z^2-xy-xz-3xy) \\ & =(x+y+z)(x^2+y^2+z^2-xy-yz-zx)\end{align}

$\endgroup$
9
$\begingroup$

Note that (can be easily seen with rule of Sarrus)$$ \begin{vmatrix} x & y & z \\ z & x & y \\ y & z & x \\ \end{vmatrix}=x^3+y^3+z^3-3xyz $$

On the other hand, it is equal to (if we add to the first row 2 other rows) $$ \begin{vmatrix} x+y+z & x+y+z & x+y+z \\ z & x & y \\ y & z & x \\ \end{vmatrix}=(x+y+z)\begin{vmatrix} 1 & 1 & 1 \\ z & x & y \\ y & z & x \\ \end{vmatrix}=(x+y+z)(x^2+y^2+z^2-xy-xz-yz) $$ just as we wanted. The last equality follows from the expansion of the determinant by first row.

$\endgroup$
7
$\begingroup$

A polynomial from $\mathbb{Q}[x,y,z]$ is a polynomial from $\mathbb{Q}[x,y][z]$, so it can be viewed as a polynomial in $z$ with coefficients from the integral domain $\mathbb{Q}[x,y]$. $$p(z)=z^3-3xy \cdot z +x^3+y^3$$

So we can try our methods to factor a polynomial of degree 3 over an integral domain: If it can be factored then there is a factor of degree $1$, we call it $z-u(x,y)$ and $u(x,y)$ divides the constant term of $p(z)$ which is $x^3+y^3$. The latter is can be factored to $(x+y)(x^2-xy+y^2)$ We check each of the possible values $(x+y), -(x+y), (x^2-xy+y^2), -(x^2-xy+y^2)$ for $u(x,y)$ and find that only $p(-x-y)=0$. So $z-(-x-y)$ is a factor.


Note:

One can use Kronecker's method

  • to reduce the factorization of a polynomial of $\mathbb{Q}[x,y,z]$ to factoring polynomials in $\mathbb{Q}[x,y]$,
  • to reduce the factorization of polynomial of $\mathbb{Q}[x,y]$ to factoring polynomials in $\mathbb{Q}[x,]$
  • to reduce the factorization of polynomial of $\mathbb{Q}[x,]$ to factoring numbers in $\mathbb{Z}$

This factoring is possible in a finite number of steps but the number of steps may become to high for practical purpose.


An integral domain is a commutative ring with $1$, where the following holds: $$a \ne 0 \land b \ne 0 \implies ab \ne 0$$ For polynomials $f$, $g$, $h$ $\in I[z]$ this guarantees: $$f=g \cdot h \implies \text{degree}(f)=\text{degree}(g) + \text{degree}(h) \tag{1}$$ compare this to $\mathbb{Z}_4$ which is no integral domain and $(2z^2+1)^2 \equiv 1$ and so $(2z^n+1) \mid 1$. So the polynomial $1$ of degree $0$ has infinitely many divisor. If $I$ is an integral domain $(1)$ guarantees that $z^3+az^2+bz+c \in I[z]$ has a linear factor and therefore zero in $I$ if it is not irreduzible.

$\endgroup$
  • $\begingroup$ Sorry but I know nothing about integral domains. Could you explain more about the $u(x,y)$ divides constant term part? $\endgroup$ – AaronS Oct 30 '13 at 0:13
  • $\begingroup$ @Aaron San: added notes about integral domains $\endgroup$ – miracle173 Nov 2 '13 at 19:27
4
$\begingroup$

$$\underbrace{x^3+y^3}+z^3-3xyz = \underbrace{(x+y)^3-3xy(x+y)}+z^3-3xyz$$

$$=\underbrace{(x+y)^3+z^3}-\underbrace{3xy(x+y)-3xyz} $$ $$=\underbrace{\{(x+y)+z\}}\{(x+y)^2-(x+y)z+z^2\}-3xy\underbrace{\{(x+y)+z\}} \left(\text{ using } a^3+b^3=(a+b)(a^2-ab+b^2)\text{ for the first two terms }\right) =(x+y+z)\{(x+y)^2-(x+y)z+z^2-3xy\}$$

Now $\displaystyle (x+y)^2-(x+y)z+z^2-3xy=x^2+y^2+z^2-xy-yz-zx$

$\endgroup$
  • $\begingroup$ Aha! Did you accidentally delete your answer before? $\endgroup$ – AaronS Nov 30 '13 at 15:53
  • $\begingroup$ @AaronS, no no. I added it a little back as it was required here(math.stackexchange.com/questions/586906/…) $\endgroup$ – lab bhattacharjee Nov 30 '13 at 15:55
  • $\begingroup$ @AaronS, I request you to not to edit so soon :). Now, I can not keep your formatting as I wanted to add inline explanation $\endgroup$ – lab bhattacharjee Nov 30 '13 at 16:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.